Influence of physical ability on initial emergency response performance - Subramaniam, Chandrakantan; Ali, Hassan; Mohd Shamsudin, Faridahwati (Emerald Group Publishing Limited, 2012)
Purpose ‐ This paper aims to determine the influence of physical ability on initial emergency response performance among emergency response teams.Design/methodology/approach ‐ In an emergency incident, emergency responders are involved in vigorous physical activities.Previous attempts have demonstrated that job performance of emergency responders depends a great deal on their ability to perform strenuous physical activity.This paper examines the influence of physical ability namely weight, height, and cardiovascular endurance on emergency response performance among fire fighting teams in Malaysia.Emergency response performance was defined as team member's speed in responding to emergency situations. Data on team member's physical ability and emergency response time were collected for the duration of five months. The distance from the waiting room to the fire truck in each selected fire station was used to measure performance.Findings ‐ This study found that the team with higher average weight and cardiovascular endurance level had better initial response to emergency situations, contrary to the research hypothesis.But it is speculated that the relationship could be further understood by considering the proportion of fat in the body.The relationship between cardiovascular endurance and initial emergency response performance further validates and justifies the use of physical fitness test as a criterion for job performance of fire fighters.Originality/value ‐ This paper offers empirical evidence of emergency response performance in Malaysia.Specifically, it presents findings on the influence of physical ability measures on initial emergency response performance from a team perspective.In addition, the emergency response performance was measured by the distance traveled by the responders, which serves as a meaningful performance indicator.